Celibacy versus Love. A Contrastive Approach to the Absence of Women among Crusaders in Prussia (Thirteenth and Fourteenth Centuries) - Murray, Alan (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2025)
This essay examines the cultural ambience of the many crusaders who travelled to Prussia to fight alongside the Teutonic Order against Lithuania in the thirteenth and fourteenth centuries. It is noticeable that a significant number of crusaders to the Levant, especially monarchs and nobles, were accompanied by their wives; by contrast, there is almost no evidence that women went on crusade to Prussia. Some factors were undoubtedly practical, but the decisive reasons are more likely to be found in the social and cultural nature of crusading in Prussia: the celibate and spiritual character of the Teutonic Order, and the changing nature of crusading itself, in which secular, chivalric values were coming to have greater weight than in the earlier crusades to the Holy Land.